LECTURER AND STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING METHOD IN WRITING CLASSROOM - Nur Maulani; Amirullah Abduh; Sultan Baa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purposes of this research were to discover the lecturer’s perception toward task-based language teaching in writing classroom, to describe how the lecturer use task-based language teaching in writing classroom and to discover the stduents’ perceptions about the impact of task-based language teaching on students’ writing achievement. This research was conducted at State University of Makassar in Makassar. This research used a qualitative method with a case study design. The technique of data analysis was carried out through the following steps: data reduction, data display and data verivication. The subjects of this research were lecturer who taught English writing and the 4th semester students at State University of Makassar. Data collection was carried out through semi-structured interview and documentation. The results of this research showed that the lecturer faced some challenges when teaching writing using TBLT such as difficulty with students who lack vocabulary and lecturer has limited time to give feedback on students’ task. In the process of classroom teaching implementation, the lecturer prepares an RPS before present the material. In evaluating teaching writing, the lecturer evaluated students’ task by identify the grammar mistakes and provide feedback on students’ task. The students feel many benefits when teaching writing using TBLT method by the lecturer such as improving their writing skills and directly practicing their writing skills. The implementation of the TBLT method should be flexible and innovative in the lecturer's approach during the writing teaching and learning process in the classroom. In addition, the majority of students appreciate the benefits of this method and the lecturers who implemented it